Empatia e pratica riflessiva come premesse alla competenza comunicativa e relazionale nel lavoro educativo con famiglie vulnerabili. Una proposta per un Syllabus didattico-formativo - Bobbo, Natascia (Rivista Italiana di Educazione Familiare, 2020)
Several pedagogical Authors already stressed that, working with vulnerable families, neither educative relationship, nor communicative act, which compose or nourish it, can exclude educators’ emphatic and introspective skills. According to this perspective, the paper therefore seeks to define a didactic Syllabus aimed at orienting teachers and tutors in implementing empathic and introspective abilities of their learners, which is based on the experiential and reflective learning approach. This propose, outlined by goals, didactic, and assessment strategies, would be a starting point for promoting wider discussions on didactic practices characterizing the learning paths of educators, students, or professionals.